"Determinants of Financial Risk Disclosure in Jordanian Commercial Banks" - الرشدان ليث; Al-Own, Bassam (The Arab Journal of Administration, 2022)
This study aimed at clarifying the determinants of financial risk disclosure in using a sample of Jordanian commercial banks listed on the Amman Stock Exchange. In order to achieve this goal, data are collected for (13) publicly listed banks in Amman Stock Exchange during the period between 2009-2018. The results of the study showed a negative and significant association between credit risk disclosure and bank size and positive and significant association between credit risk disclosure and financial leverage. However, the results show no significant linkage between credit risk disclosure and each of profitability and age of the bank. The results of the analysis also revel that liquidity risk disclosure is negatively associated with bank size, and positively associated with bank age. In addition, the results show no relationship between liquidity risk disclosure and each of leverage and profitability. This study concludes that several factors play important role in determining financial risk disclosure in Jordanian banking sector. However, Supervisors and regulators are recommended to develop strategies that help to provide a proper publicly disclose information about financial risk in order to help market participants to make an effective assessment of the soundness of banking financial risk. Moreover, further research studies similar in nature to this study can be helpful in determining key factors that influence financial risk disclosure which improve the quality of disclosed information in the banking industry.